Assessing the literature of knowledge management (KM) in the field of library and information science. Issue 1 (1st March 2019) - Ahmad, Khurshid; JianMing, Zheng; Rafi, Muhammad
Abstract : Purpose: The purpose of this study is to provide a bibliometric analysis of knowledge management (KM) literature published in the field of library and information science. KM is a systematic process of acquisition, extraction, organization and dissemination of knowledge in any organization. This study will help identify trends, emerging concepts and innovations in this particular field. Design/methodology/approach: The data set of the study consists of 6, 088 published documents the authors obtained from the ISI Web of Science database during 1900 and 2017. The analysis of literature about the library and information science consisted of five categories including productive institutions, prolific authors, annual publications, citations and highly cited articles. The documents included in this study include research papers, conference papers, reviews, book reviews and editorials. Findings: The study found that the USA leads the world regarding the number of research publications in the area of KM in the field of library and information science. Considering the publication period, 2007, 2012 and 2016-2017 are the most productive years regarding publications in this particular field; the number of citations has been increasing over the years. The study also found that Nanyang Polytechnic University is the most productive research institution and Blanca Martins from the Polytechnic University of Catalonia is the most prolific researcher in this specific field. Originality/value: This study provides a detailed bibliometric analysis of KM literature published in the field of library and information science. This study is an excellent example for researchers who are interested in conducting bibliometric studies.